2018
DOI: 10.1002/er.4200
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on parametric dependencies of transpired solar collector performance

Abstract: Summary Zero or low‐carbon buildings can be achieved through novel technology solutions and integrating renewable energy into the buildings. One method of reducing the fossil fuel dependency of buildings and limiting greenhouse gas emissions is integrating the solar thermal system into the built environment. Recently, transpired solar collector has been identified as 1 of the most efficient solar thermal conversion technologies where a very high efficiency can be achieved. The proposed review paper investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…RNG k-ε turbulence model combined with Enhanced Wall Treatment option has been set. For this particular type of study, namely Transpired Solar Collectors, RNG k-ε turbulence model seems to be a good choice as a turbulence model regarding the accuracy, numerical stability, and computing time (Bake et al, 2019; Bejan et al, 2019c; Bode et al, 2020; Li et al, 2013; Wang et al, 2017). These modeling techniques improve the convergence and accuracy of results especially for cases with low y +, which is our situation.…”
Section: Methodsmentioning
confidence: 99%
“…RNG k-ε turbulence model combined with Enhanced Wall Treatment option has been set. For this particular type of study, namely Transpired Solar Collectors, RNG k-ε turbulence model seems to be a good choice as a turbulence model regarding the accuracy, numerical stability, and computing time (Bake et al, 2019; Bejan et al, 2019c; Bode et al, 2020; Li et al, 2013; Wang et al, 2017). These modeling techniques improve the convergence and accuracy of results especially for cases with low y +, which is our situation.…”
Section: Methodsmentioning
confidence: 99%
“…According to the literature, the RNG k-ε turbulence model is the most appropriate and reasonable when considering accuracy and computing time for numerical simulations regarding Transpired Solar Collectors [13,19,20]. Thus, we set the RNG k-ε turbulence model combined with the Enhanced Wall Treatment option including thermal effects and pressure gradients.…”
Section: Model Configurationmentioning
confidence: 99%
“…Other parameters, like the pressure drop inside the solar collectors, show a significant role in the design of such systems [12]. It has been found that wind speed and airflow rate are the most influent parameters on transpired solar collector performance [13]. Seminal contributions have been made by Croitoru et al regarding the influence of the perforation shapes on the absorber plate [14], showing that round holes have lower heat transfer than lobed geometries by about 15%.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the utilization of natural lighting in skylights and classrooms, the rated power consumption totals up to be a mere 8% of the total rated power for the whole university. Other utilitarian consumers are the data centre, elevators, chilled water T A B L E 2 Comparative study of BIPV work and the proposed research highlight 19,[41][42][43][44][45][46][48][49][50][51][52][53][54][55][56][57][58][59][60] No. Predicted energy outputs from array side and grid input side decrease in a few months because of influence from weather parameters, module temperature, and other system components.…”
Section: Energy Statistics and Analysismentioning
confidence: 99%